PSYCHOLOGICAL PECULIARITIES OF THE CHILDREN, SUFFERING FROM THE PEPTIC ULCER DISEASE - I.E. Sulaberidze; O.K. Botvin'ev (Педиатрическая фармакология, 2007)
The objective of this work was to reveal the psychological peculiarities of the children, suffering from the peptic ulcer disease. The research findings disclosed considerable changes in the psychological status of these children, which is a sufficient ground for the application of medications, corarecting the psychological deviations.Key words: children, psychological status, deviations, peptic ulcer disease.